2021
DOI: 10.1177/14680874211034682
|View full text |Cite
|
Sign up to set email alerts
|

Effect of injection and ignition timing on a hydrogen-lean stratified charge combustion engine

Abstract: Hydrogen can be used as a fuel for internal combustion engines to realize a carbon-neutral transport society. By extending the lean limit of spark ignition engines, their efficiency, and emission characteristics can be improved. In this study, stratified charge combustion (SCC) using monofueled hydrogen direct injection was used to extend the lean limit of a spark ignition engine. The injection and ignition timing were varied to examine their effect on the SCC characteristics. An engine experiment was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…An optimized directinjection strategy results in a higher engine efficiency and lower NOx production. Delaying the Start of Injection (SOI) produces a stratified mixture, 5 with a 1 Department of Mechanics, Mathematics and Management -Politecnico di Bari, Bari, Italy 2 rich mixture near the spark and a lean one close to the walls. 6 In this way, wall heat losses and the mean cycle temperature are reduced, resulting in near-to-zero NOx emissions.…”
Section: Introductionmentioning
confidence: 99%
“…An optimized directinjection strategy results in a higher engine efficiency and lower NOx production. Delaying the Start of Injection (SOI) produces a stratified mixture, 5 with a 1 Department of Mechanics, Mathematics and Management -Politecnico di Bari, Bari, Italy 2 rich mixture near the spark and a lean one close to the walls. 6 In this way, wall heat losses and the mean cycle temperature are reduced, resulting in near-to-zero NOx emissions.…”
Section: Introductionmentioning
confidence: 99%
“…A common observation from the previous research is that the engine efficiency improves by boosting, while NO x emission increases. Lee et al 25 had observed retarded ignition to reduce NO x slightly; similarly, Zareei and Ghadamkheir 26 had also reported a slight drop in NO x emission with retarded ignition. However, the NO x reduction was not satisfactory under minimum performance drop range.…”
Section: Introductionmentioning
confidence: 93%
“…Papers in the no-carbon emission group touch on topics such as: the efficiency of hydrogen fuel cell vehicles under real-world operating conditions, 1 the use of hydrogen in internal combustion engines in both spark-ignited and compression ignition operation, [2][3][4] the concept of a split-cycle hydrogen engine with argon as the working fluid 5 and the use of ammonia in a spark-ignited engine. 6 A number of papers focused on intermediate-term solutions that would be accompanied by some engine-out carbon emissions.…”
Section: Introduction To the Current And Future Use Of H2 And H2-base...mentioning
confidence: 99%
“…the use of hydrogen in internal combustion engines in both spark-ignited and compression ignition operation, 24…”
mentioning
confidence: 99%